Patient periprocedural stress in cardiovascular medicine: friend or foe? - Iwaszczuk, Paweł; Łosiak, Władysław; Szczeklik, Wojciech; Musiałek, Piotr (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
Stress, a disruption of homeostasis, is an unavoidable part of everyday life. In medical procedures, stress profoundly affects both operators and patients. Although the stress reaction has evolved to aid survival of physical trauma, it may also be harmful, by aggravating the baseline medical condition and/or creating new stress-related medical problems. Stress responses comprise several protective mechanisms that are particularly relevant in the clinical setting (e.g., a procoagulatory state and blood loss counteraction, preservation of blood perfusion pressure, prevention of hypoglycemia, enhanced immune response). Beneficial psychological effects prevent recurrence of traumatic memories, and promote patient compliance and positive lifestyle changes. In contrast, overt acute stress responses may lead to severe pathological conditions such as cytokine storm, post-traumatic stress disorder, takotsubo syndrome, deep venous thrombosis and pulmonary embolism, myocardial infarction, life-threatening arrhythmias and sudden cardiac death. There is also evidence that stress exposure may promote atherosclerosis and reduce long-term benefits from the intervention (increase in major adverse clinical events, in-stent restenosis, etc.). Insights into the role of stress on the operator’s performance have recently led to the introduction of counteractive measures such as simulation training. Conversely, very little is known about the effect of the patient’s periprocedural stress on the outcomes of cardiovascular procedures. Recent data show that the patient periprocedural stress affects the well-being of whole families. This review, focused on topics particularly relevant to cardiovascular interventions, provides a mechanistic insight into beneficial and harmful effects of periprocedural patient stress, including the array of available stress-relieving measures.